Case Report: Conservative Non-operative Management of a Neonate With Torted Wandering Spleen - Bourusly, Maha; Ayed, Mariam; Bahzad, Zainab (Frontiers in Pediatrics, 2022)
Background: Wandering spleen (WS) with torsion, a rare pathological condition has unclear management. Most patients with this disorder are usually treated with surgical interventions such as splenectomy or splenopexy. Case presentation: A newborn female presented with low hemoglobin (10.8 mg/L), and high total serum bilirubin (193μmol/L; at 3 hours of life). A palpable mass was observed during her physical examination, and a magnetic resonance imaging scan of the abdomen confirmed the presence of an infarcted WS with torsion. Upon conservative management with oral antibiotics prophylaxis, careful observation, scheduled routine vaccination, and repeated follow-ups, the infant remained clinically stable. At 2 years of age, she had normal complete blood counts, and a repeat of technetium study revealed two splenunculi/splenules in the splenic bed. Conclusion: Non-operative management may be a feasible treatment option in a few selected cases with infarcted WS and may allow the natural process of auto-splenectomy to occur.